Targeting aging hallmarks in brain health within the framework of preventive medicine: mechanistic insights into naringenin’s role in longevity, synaptic function, and cellular homeostasis - Zhi, Yong; Xie, Shanshan; Sun, Yanting (Frontiers in Nutrition, 2026)
Aging is the primary driver of neurodegenerative vulnerability and functional decline in the brain. This narrative review synthesizes preclinical in vitro and in vivo evidence on naringenin, a citrus-derived flavonoid with pleiotropic effects on aging-related pathways. Naringenin modulates oxidative stress, enhances mitochondrial efficiency, and supports neurotrophic signaling linked to synaptic integrity and cognitive resilience. Experimental studies consistently show activation of Nrf2, SIRT1, and PI3K/Akt pathways, attenuation of neuroinflammatory cascades, and restoration of redox and proteostatic balance. Through these integrated actions, naringenin targets several hallmarks of brain aging, including mitochondrial dysfunction, oxidative stress, and impaired cellular homeostasis. From a preventive medicine perspective, understanding these mechanisms may guide the development of safe, dietary interventions aimed at promoting healthy brain aging and delaying neurodegenerative processes.